Edible films enriched by elamin - Chorna, Anastasia; Shulga, Oksana; Arsenieva, Larisa; Petrenko, Olena (My University, 2016)
The analysis of results shows that it is sufficient to use 1.5% of elamin in edible films to enrich bakery products in iodine. The indicated concentration allows to enrich a product with iodine in the amount that fully meets the iodine daily requirements.
Keywords: їстівні плівки; еламін; сьедобная пленка; эламин; edible film; elamin; кафедра експертизи харчових продуктів; Інститут Марзєєва